Productive Waqf, Economic Empowerment, and Public Welfare: Evidence from Benefit Recipients at Daarut Tauhiid Waqf Institution - Wildan Munawar; M Arief Mufraini (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2021)
This study aimed to determine the effect of productive waqf management on public welfare with economic empowerment as an intervening variable. The research method used quantitative research, and the data collection used a closed-ended questionnaire. The sampling was selected based on the purposive sampling technique by determining certain criteria and objectives. The data analysis technique used Partial Least Square (PLS) with the PLS 3 smart application. The results of this study concluded that productive waqf management had a positive and significant effect on public welfare with economic empowerment as an intervening variable. The better the management of productive waqf carried out by the waqf institution, the more indirectly it would improve the public welfare with good economic empowerment. The good of productive waqf management can be used as a benchmark for waqf institutions in managing waqf. This was because past experience and history have proven that well-managed waqf improved public welfare through economic empowerment carried out consistently. However, not only through the cultivation of worship and Islamic character but also supported by skills and training in business improvement, mentoring, and monitoring of business operations, as well as providing business and marketing capital.